2021
DOI: 10.1093/aje/kwab027
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Lifestyle and Anthropometric Factors With the Risk of Herpes Zoster: A Nationwide Population-Based Cohort Study

Abstract: The role of lifestyle in development of herpes zoster remains unclear. We examined whether smoking status, alcohol consumption, body mass index (BMI), or physical activity were associated with zoster risk. We followed a population-based cohort of 101,894 respondents to the 2010 Danish National Health Survey (baseline May 1, 2010) until zoster diagnosis, death, emigration, or July 1, 2014, whichever occurred first. We computed hazard ratios for zoster associated with each exposure, using Cox regression with age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…We also found that performing moderate physical activity seven days per week increased the risk of HZ by 29% compared to those who did not exercise. These findings are not consistent with previous epidemiological studies examining physical activity as a possible risk factor for HZ, which found no association [ 32 , 33 ]. However, research suggests that vigorous physical activity may be immunosuppressive [ 34 ], and hence, could potentially play a role in the reactivation of varicella zoster through this mechanism.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also found that performing moderate physical activity seven days per week increased the risk of HZ by 29% compared to those who did not exercise. These findings are not consistent with previous epidemiological studies examining physical activity as a possible risk factor for HZ, which found no association [ 32 , 33 ]. However, research suggests that vigorous physical activity may be immunosuppressive [ 34 ], and hence, could potentially play a role in the reactivation of varicella zoster through this mechanism.…”
Section: Discussioncontrasting
confidence: 99%
“…Other demographic and lifestyle factors, including deprivation, BMI, smoking and alcohol consumption were found to have no association with HZ. This is consistent with previous research examining the role of lifestyle and anthropometric factors and risk of zoster [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Third, smoking status is not provided in the NHI research database. One study reported that former smokers were 1.17 times more likely to develop HZ than those who had never smoked [ 30 ]. Thus, outcomes may have been overestimated or underestimated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not clear how lifestyle and behavioral changes and the associated stress affect the incidence of HZ [25][26][27], we examined how lifestyle and behavioral changes for preventing COVID-19 spread in 2020 affected HZ epidemiology. Since a total of 757 COVID-19 patients were recorded on December 31, 2020 and COVID-19 vaccine was not available in 2020 [18], the HZ incidence change is among the general population and not in J o u r n a l P r e -p r o o f Table 112 patients with COVID-19.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%